2012
DOI: 10.1158/1055-9965.epi-11-1017
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Risk in Men with Baseline History of Coronary Artery Disease: Results from the REDUCE Study

Abstract: Background: Coronary artery disease (CAD) and prostate cancer (PCa) are not only common diseases, but share many risk factors. To date, only a few studies have explored the relationship between CAD and PCa risk, with conflicting results.Methods: The four-year REDUCE study tested dutasteride 0.5 mg daily for PCa risk reduction in men with prostate specific antigen (PSA) of 2.5 to 10.0 ng/mL and a negative biopsy. Among men who underwent at least one on-study biopsy (n ¼ 6,729; 82.8%), the association between CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 28 publications
5
42
0
3
Order By: Relevance
“…In REDUCE study vascular disease was associated with an increased risk of PCa diagnosis (OR = 1.35) [32]. Our findings also are consistent with autopsy study of Stamatiou suggesting that men with PCa had greater advanced atheromatosis than subjects without PCa [30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In REDUCE study vascular disease was associated with an increased risk of PCa diagnosis (OR = 1.35) [32]. Our findings also are consistent with autopsy study of Stamatiou suggesting that men with PCa had greater advanced atheromatosis than subjects without PCa [30].…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, only a few studies have explored the relationship between vascular disease and PCa risk, with inconclusive results [14]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…In a case-control study in 1294 Italian men <75 years of age with incident PrC compared to 1451 men hospitalized with acute, non-neoplastic conditions, the odd ratio (OR) for prostate cancer was 1.54 (95% CI, 1.26-1.89) for those with hypercholesterolemia (Pelucchi, Serraino et al 2011). A post hoc analysis of the REDUCE study (which evaluated the anti-testosterone dutasteride in men with high prostate specific antigen (PSA) values but no PrC) examined the association of coronary artery disease (CAD) with PrC risk (Thomas, Gerber et al 2012). In 6729 men who underwent at least one biopsy, those with CAD had an increased risk of PrC diagnosis (OR = 1.35, 95% CI, 1.08-1.67), suggesting common risk factors.…”
Section: Clinical and Epidemiological Evidence For An Association Of mentioning
confidence: 99%
“…For example, the presence of cardiovascular disease may increase the risk of prostate cancer as it shares common risk factors for the development of aggressive prostate cancer, such as the presence of high cholesterol level and obesity. 9,10 Few studies have investigated the relationship between specific types of chronic conditions and cancer stage at diagnosis. Findings from these studies suggest that the association between preexisting chronic conditions and cancer stage at diagnosis depends on the types of chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] With respect to mental health conditions, a retrospective study found that elderly men with depression were not more likely to be diagnosed with a higher grade of prostate cancer compared to those without depression. 9 Although these studies have highlighted the relationship between specific chronic conditions and cancer stage at diagnosis, many of these studies are outdated, single-institution database studies and suffer from the risk of detection bias because screening for prostate cancer was not included as one of the independent variables. [5][6][7] Furthermore, none of these studies examined the association between types of chronic condition combinations and cancer stage at diagnosis among elderly men.…”
Section: Introductionmentioning
confidence: 99%